Reaganism, Thatcherism and the Social Novel - Hutchinson, C. author. aut Link
IX, 207 p.
Keywords: The social novel is the traditional haunt of the liberal conscience. What does the triumph of the New Right mean for this type of fiction in Britain and the US? Should the liberal left seek consensus or assertion? This book examines these issues, and assesses the state of both nations, as well as that of the contemporary novel.